Pulmonary Embolism presenting as Syncope - Mall, Dipak; Shaning, Yang (Nepalese Heart Journal, 2015)
The diagnosis of Pulmonary embolism can easily be missed if it is not considered as one of the major differential diagnosis in a case of syncope without chest pain. We describe a case of a 74years old female with pulmonary embolism induced syncope, which highlights one of the difficulties in diagnosing pulmonary embolism. In a patient presenting in syncope without chest pain but raised troponin, the possibility of pulmonary embolism should also be considered if it does not fit with myocardial infarction. Otherwise, the diagnosis can be easily missed and patients may not receive appropriate treatment resulting in increased mortality. Pulmonary embolism should be considered in the differential diagnosis of every syncopal event in Emergency department and Cardiac care units. DOI: http://dx.doi.org/10.3126/njh.v12i1.12343 Nepalese Heart Journal Vol.12(1) 2015: 37-41